2016
DOI: 10.15353/cfs-rcea.v3i1.72
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to acquiring and utilizing food literacy: Perceptions of young Canadian adults

Abstract: The purpose of this qualitative, grounded theory study was to explore the concept of food literacy from the perspective of young Canadian adults who recently transitioned to independent living. Seventeen individual, in-depth interviews were conducted with Canadian university students from this target group. Results suggest that young adults face significant challenges with regard to healthy eating as well as acquiring and using food literacy. The three main reasons for these challenges were: a lack of food and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 12 publications
5
54
0
Order By: Relevance
“…This confirms others' conclusions about the importance of learning cooking/food skills early [8,11]. Similarly, university students who participated regularly in food-related activities in their parental home described themselves as having a high level of food literacy [3,7]. Another important finding was that having taken an FN course remained a significant predictor of students' TFSS across all 4 regression models, suggesting that FN education should occur well before young adults begin living independently [12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This confirms others' conclusions about the importance of learning cooking/food skills early [8,11]. Similarly, university students who participated regularly in food-related activities in their parental home described themselves as having a high level of food literacy [3,7]. Another important finding was that having taken an FN course remained a significant predictor of students' TFSS across all 4 regression models, suggesting that FN education should occur well before young adults begin living independently [12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, many prepare meals less than once per week [2]. Small qualitative studies have found that minimal hands-on food participation while growing up may contribute to this situation [3], and that few students get into the habit of checking current food stocks, making shopping lists, and grocery shopping [4]. This is unfortunate, as the use of a grocery list has been associated with a healthier diet and lower body mass index (BMI) [5] and higher consumption of fruits and vegetables [6].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing rates of diet-related disease has been linked to an apparent decline in the general population’s food knowledge and skills [1,2]. A plethora of commentaries on this association exist in the literature, with authors describing a “gastronomic revolution” [3], an “epidemic of culinary ineptness” [4] and a “dietary cacophony" of conflicting information that “deadens” an individual’s capacity to eat [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of a growing ultraprocessed food supply and culinary deskilling, amid numerous "healthy eating" messages, have created confusion for citizens who must navigate the complex modern foodscape (Escott-Stump, 2011;King et al, 2012). These trends have led to a call to invest in building fundamental food and nutrition knowledge and skills in the population (Colatruglio & Slater, 2016;Lichtenstein & Ludwig, 2010;Pendergast & Dewhurst, 2012;Slater, 2013). Existing studies indicate that early in-home food experiences have a positive impact on food skills (Laska et al, 2011), and increased diet quality is associated with greater frequency of cooking and the use of more complex steps when preparing meals (Larson, Story, Eisenberg, & Neumark-Sztainer, 2006;Moubarac et al, 2013;Thorpe, Kestin, Riddell, Keast, & McNaughton, 2014).…”
mentioning
confidence: 99%
“…Food literacy has emerged as a broader concept which may confer protective benefits in the context of the modern foodscape (Colatruglio & Slater, 2016;Cullen, Hatch, Martin, Higgins, & Sheppard, 2015;Krause, Sommerhalder, Beer-Borst, & Abel, 2016;Slater, 2013;Sumner, 2015;Vidgen & Gallegos, 2010). Vidgen and Gallegos have examined the components of food literacy from the perspective of young adults, focusing on the day-to-day experiences of feeding themselves, as well as food experts' understanding of the term "food literacy" (Vidgen & Gallegos, 2014).…”
mentioning
confidence: 99%